PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN PSIKOLOGIS DIDALAM RUMAH TANGGA DARI ORANG TUA (Lex Journal: Kajian Hukum & Keadilan, 2019)
Domestic violence  is a classic problem in the world of law and gender. Althougt the legal umbrella for protecting victim from domestic violence is already existing, namely law number 23 of 2004 concerning the elimination of domestic violence, this is not enough to anticipate the violence in this chase the need  for attention and legal protection for government, law enforcement officer, and from the community so that everyone who hears, sees, or knows about the occurrence of domestic violence is obligated to take preventive measure and provide assintance. actually what is the cause and what kind of protection for women victim of criminal acts of violence in the hosehold that are regulated in indonesia positive law.keywords: legal protection, domestic violence